2009
DOI: 10.1074/jbc.m109.012526
|View full text |Cite
|
Sign up to set email alerts
|

Src-dependent STAT-3-mediated Expression of Monocyte Chemoattractant Protein-1 Is Required for 15(S)-Hydroxyeicosatetraenoic Acid-induced Vascular Smooth Muscle Cell Migration

Abstract: VSMC3 migration from media to intima plays a determinant role in atherosclerosis and restenosis (1-3). Arachidonic acid (AA) and its oxygenated metabolites, collectively known as eicosanoids, are involved in the maintenance of vascular tone (4, 5). Lipoxygenases (LOXs) are non-heme iron dioxygenases that stereospecifically introduce molecular oxygen into polyunsaturated fatty acids, resulting in the formation of hydroperoxyeicosatetraenoic acids, which are subsequently converted to hydroxyeicosatetraenoic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
62
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 61 publications
4
62
0
Order By: Relevance
“…As observed in the case of HASMCs, these findings also infer that NFATc1 acts downstream to Rac1 in mediating cyclin D1 expression, CDK6 and CDK4 activities, and Pak1 activation in the modulation of mouse VSMC migration and proliferation. We have reported previously that injury induces MCP1 expression in a rat carotid artery injury model (12). In agreement with this observation, guide wire injury induced MCP1 expression in the carotid artery, mostly in SMCs, of both WT and SM22Cre:NFATc1 fl/fl mice.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…As observed in the case of HASMCs, these findings also infer that NFATc1 acts downstream to Rac1 in mediating cyclin D1 expression, CDK6 and CDK4 activities, and Pak1 activation in the modulation of mouse VSMC migration and proliferation. We have reported previously that injury induces MCP1 expression in a rat carotid artery injury model (12). In agreement with this observation, guide wire injury induced MCP1 expression in the carotid artery, mostly in SMCs, of both WT and SM22Cre:NFATc1 fl/fl mice.…”
Section: Discussionsupporting
confidence: 72%
“…Formation, Migration, and Proliferation-We have reported previously that vascular injury produces MCP1 and that it mediates VSMC migration and proliferation (12,13). In addition, we have demonstrated that MCP1-induced VSMC migration and proliferation require PKN1 (22), a Rho GTPase effector (30).…”
Section: Pak1 Mediates Mcp1-induced Hasmc F-actin Stress Fibermentioning
confidence: 92%
See 1 more Smart Citation
“…Interestingly, 15-HETE, the major 15-LO product of AA, was also found to be the major metabolite of AA converted by the atherosclerotic arteries (12,13). Similarly, we have reported that overexpression of 15-LO1 or 15-LO2 exacerbates restenosis in response to injury (49,50). In addition, the previous studies by us as well as others have reported the presence of 15-LO or its inhibitor, nordihydroguaiaretic acid-sensitive production of 15(S)-HETE and 13(S)-hydroxyoctadecadienoic acid in response to incubation with AA and linoleic acid, respectively, in both vascular smooth muscle cells and endothelial cells (28,(51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 72%
“…16,40 Recently, we have shown that forced expression of 15-LOX2 in rat vascular smooth muscle cells or 15-LOX1 in balloon-injured arteries led to production of only 15(S)-HETE. 41,42 Many reports also revealed that angiogenesis plays a critical role in the progression of atherosclerosis and restenosis. 34,35 Our findings showed that 12/15-LOX Ϫ/Ϫ mice fail to exhibit an angiogenic response to AA compared with WT mice.…”
Section: Discussionmentioning
confidence: 99%